Clinicopathological features and surgical outcomes of four rare subtypes of primary liver carcinoma - Li, Zhiyu (Chin J Cancer Res, 2018)
OBJECTIVE: This study aimed to analyze clinicopathological and prognostic features of four rare pathological subtypes of primary liver malignancies to make better understanding of their clinical features. METHODS: The clinicopathological data of 114 patients who were diagnosed with histologically proven four subtypes: clear cell carcinoma (CCC), giant cell carcinoma (GCC), sarcomatoid carcinoma (SC), and combined hepatocellular-cholangiocarcinoma (CHC) between October 1998 and August 2015 were reviewed. Their survival data were compared with those of 908 patients with histologically proven common hepatocellular carcinoma (HCC) (early- and advanced-stage HCC) during the same period. RESULTS: The outcome of the CCC group was better than that of the other three subgroups, and was similar to that of the early-stage HCC group. Also, the smallest tumor size and the highest incidence of pseudocapsule formation were observed in the CCC group. The SC group had the worst outcome among these four subgroups; the prognosis was much poorer than that of any other subgroups, even poorer than that of the advanced-stage common HCC group. No statistical difference was observed between the GCC, CHC and advanced-stage HCC groups on survival analysis. The incidences of tumor vascular emboli, TNM staging and non-radical resection were three risk factors of the prognosis. CONCLUSIONS: CCC is a low-degree malignancy and relatively favorably prognostic subtype of HCC. However, GCC, SC, and CHC are three rare high-degree malignancy subtypes of HCC with poor prognosis.